Targeting skeletal endothelium to ameliorate bone loss. (June 2018) - Xu, Ren; Yallowitz, Alisha; Qin, An; Wu, Zhuhao; Shin, Dong; Kim, Jung-Min; Debnath, Shawon; Ji, Gang; Bostrom, Mathias; Yang, Xu; Zhang, Chao; Dong, Han; et al.
Abstract Recent studies have identified a specialized subset of CD31hi endomucinhi (CD31hi EMCNhi ) vascular endothelium that positively regulates bone formation. However, it remains unclear how CD31hi EMCNhi endothelium levels are coupled to anabolic bone formation. Mice with an osteoblast-specific deletion ofShn3, which have markedly elevated bone formation, demonstrated an increase in CD31hi EMCNhi endothelium. Transcriptomic analysis identified SLIT3 as an osteoblast-derived, SHN3-regulated proangiogenic factor. Genetic deletion ofSlit3 reduced skeletal CD31hi EMCNhi endothelium, resulted in low bone mass because of impaired bone formation and partially reversed the high bone mass phenotype ofShn3 −/− mice. This coupling between osteoblasts and CD31hi EMCNhi endothelium is essential for bone healing, as shown by defective fracture repair in SLIT3-mutant mice and enhanced fracture repair in SHN3-mutant mice. Finally, administration of recombinant SLIT3 both enhanced bone fracture healing and counteracted bone loss in a mouse model of postmenopausal osteoporosis. Thus, drugs that target the SLIT3 pathway may represent a new approach for vascular-targeted osteoanabolic therapy to treat bone loss. Recombinant SLIT3 represents a new mechanistic approach to treating osteoporosis by increasing skeletal CD31hi EMCNhi vascular endothelium.